Sustainable concrete construction proceedings of the international conference held at the University of Dundee, Scotland, UK on 9-11 September, 2002 - Dhir, Ravindra K.; Dyer, Thomas D.; Halliday, Judith E. (Thomas Telford, 2002)
There is no substitute for concrete that can be used on the same engineering scale. Its sustainability, exploitation and further development are necessary for a healthy economy and environment worldwide. Concrete must keep evolving to satisfy the increasing demands of all its users.